Alternative Procedures for Reducing Delays in Criminal Appeals: Sacramento, Springfield, and Rhode Island, 1983-1984 - Chapper, Joy A. ([Verlag nicht ermittelbar], 1993)
This data collection investigates the effectiveness of alternative approaches to reducing delays in criminal appeals. Interviews were conducted with court representatives from districts employing differing alternatives. These districts and approaches are (1) case management in the Illinois Appellate Court, Fourth District, in Springfield, (2) staff screening for submission without oral argument in the California Court of Appeals, Third District, in Sacramento, and (3) fast-tracking procedures in the Rhode Island Supreme Court. Parallel interviews were conducted in public defenders' offices in three additional locations: Colorado, the District of Columbia, and Minnesota. Questions focused on the backlogs courts were facing, the reasons for the backlogs, and the consequences. Participants were asked about the fairness and possible consequences of procedures employed by their courts and other courts in this study. Case data were acquired from court records of the Springfield, Sacramento, and Rhode Island courts.